MODEL PENELITIAN TOKOH (Dalam Teori dan Aplikasi) - Mustaqim, Abdul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2014)
The author explores some ways and its importance to biographical study in the Qur’an and Hadith. The purpose of research on biographical studies is to achieve a comprehensive understanding of the thoughts, ideas, concepts, and theories of someone he examined. The considerations in conducting this kind of research, among others, for example, his/her controverciality, influence, popularity, uniqueness, the intensity on the field of study that would scrutinized, relevance and contributions of his/her thinking in the context of the present.